(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2023)
This article, entitled “Cultural Governance: The Sandinista Good Government Management Model for Democratizing Artistic and Cultural Diversity”, aims to demonstrate the management of cultural governance with democratic praxis, that drives the local authorities of the municipality of Ciudad Sandino, in order to promote the exercise of the rights of citizens to claim, promote and enjoy an artistic and cultural diversity of their own roots. The analysis takes as a reference framework: the situation of artistic and cultural work that is being promoted by U NESCO at the international level, in order to strengthen human talent and sustainable development, in order to comply with the SDGs. It also recognizes the model of government being worked on in Nicaragua, through the National Plan to Fight Poverty and Human Development 2022-2026, and the cultural policies proposed by the Sandinista Government, that together are articulated to a democratic model that allows the participation and promotion of artistic and cultural diversity, in order to generate proposals of economic values with cultural relevance. And at the local level, from the Municipality of Ciudad Sandino, the Electoral Plan 2023-2026 is taken up, which promotes the guidelines of work, in order to manage the development of Sandinista arts and culture.